Climate Change and Economic Vulnerability in Pakistan: An Analysis of Future Risks - Sukanta Sarkar (International Journal of Climate Conditions, 2024)
This paper discussed effects of climate change on economic vulnerability in Pakistan. The findings show that the nation's economy is negatively impacted by climate change. Poverty, unemployment, crime, forest fire, diseases, migration, internal displacement, urban slum, flood etc. will be increase in future due to climate change. Biodiversity and economic balance will be disturbed. Food production, electricity supply, basic infrastructure will be badly affected. Development activities in water resources, as well as sectors such as agriculture, and health could clearly be affected by climate change as well as current climate variability. Fluctuation of climate variables influences the spread of infectious disease. Incidences of fresh flood or glacial lake outburst floods will be increase. Due to climate change industrial production will be affected for the shortage of raw materials and unfavourable climates. Agro-based industries and service sector will be more effected. As a result, the government will need extra funding for disaster relief. The government should establish robust policies that encourage community-based adaptation strategies, make investments in sustainable development, improve climate resilience, raise public awareness, fortify institutional frameworks, and incorporate climate change adaptation into local and national planning procedures in order to lessen the negative effects of climate change on the economy. Furthermore, creating a collaborative environment with stakeholders and international organizations will be essential to creating comprehensive plans for climate action.
Keywords: Climate change; Global Warming; adaptation strategies; disaster management; economic vulnerability; natural calamities